The army of Alexander the Great and combat stress syndrome (326 BC) - Retief, Francois P.; Cilliers, Louise (Acta Theologica, 2005)
In the summer of 326 BC, Alexander the Great’s triumphal seven-year campaign in Asia was unexpectedly halted in the upper reaches of the Indus river — not by enemy action, but by the troops’ refusal to march further eastwards. A possible reason for such drastic action by an army which had, until that point, followed its king with blind devotion, was that severe combat stress may have set in. This syndrome, as it is defined today, has been thoroughly researched. The present article investigates the possibility that combat stress perhaps provides an explanation for this dramatic occurrence in which Alexander’s dream of an empire extending to the ends of the earth was shattered.